The Heritage of the Textile Industry, A Thematic Study for TICCIH, The International Committee for the Conservation of the Industrial Heritage: by Heike Oevermann, Bartosz M. Walczak and Mark Watson, Lodz, The Lodz University of Technology, 2022, pb, 192 pp. ISBN 978-83-66741-23-2 (not available as hard copy, but can be downloaded from https://repozytorium.p.lodz.pl/handle/11652/4237) - Preite, Massimo (Industrial Archaeology Review, 2023)
It is an exhortation that has not fallen on deaf ears, if we think of the new studies published in recent years, those on the water industry (2019), on the oil industry (2020) and, finally, the last one in order of time, that on the I Heritage of the Textile Industry i , edited by Heike Oevermann, Bartosz Walczak and Mark Watson (2022). Bearing in mind that Table 1 shows that there are only eight textile sites on the World Heritage List, of which only two are located outside Europe, it is easy to foresee that this inventory will have to be drawn upon for new entries, whether or not it is considered that a more "representative, balanced and credible" presence of the textile industry on the World Heritage List is to be undertaken as soon as possible. 192 pp.